IMPLEMENTASI METODE REWARD AND PUNISHMENT PADA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM DI SMP ISLAM NUR HIDAYAH BALIKPAPAN - Akhmad Robayt Alfauzi; Indhra Musthofa; Qurroti Aâ€™yun (VICRATINA, 2022)
The research with the title of implementing the reward and punishment method in Islamic religious education subjects at Nur Hidayah Islamic Middle School Balikpapan aims to describe the planning, implementation and results of the implementation of the reward and punishment method at Nur Hidayah Islamic Junior High School Balikpapan. The method used in this research is qualitative research. The results of this study are: 1) PAI teachers plan a reward and punishment method that is combined in lesson plans, syllabus, semester programs, annual programs and academic calendars to support learning objectives. (2) at the stage of implementing the reward and punishment method, the teacher gives rewards as a tool education, not as wages. Whereas in giving punishment, the teacher does not directly impose punishment on students, but considers it first, resulting in changes in behavior expected by the teacher. 3) the benchmark for the success of PAI learning using the reward and punishment method can be seen through three aspects, namely cognitive, affective and psychomotor.Â Kata Kunci: metode, reward and punishment, pendidikan agama IslamÂ